DEVELOPMENT OF TRANSGENIC DUCKWEED EXPRESSING VP2 ANTIGEN AND THE PRELIMINARY IMMUNOLOGICAL IN TEST CHICKENS - Hàm, Lê Huy (Vietnam Journal of Biotechnology, 2011)
VP2 is an antigenic gene that has had a very wide range utilized potential for producing a new generation of vaccine and actively designing way in vaccine strategy for combating gumboro disease. In the last decade, ',f there are many researches from over the world have shown great applied potential of edible vaccines produced through transgenic plants. Not only they contribute to cost reduction, they opened up new prospects in applying plant biotechnology to agriculture, medicine and many aspects of life, also. The aim of this research is to regenerate transgenic duckweeds with VP2 as a transgene which can produce recombinant proteins as a (,j vaccine. VP2 gene was transferred into Wolffia australiana by an A. tumefaciens GV3101 strain which .*[ contains pPAM-VP2 vector. After transformation, W. australiana plants were selected by placing onto a ji, medium added 30 mg/l geneticine. Twenty transformation events of Wolffia australiana were obtained after four cycles of selection. These transformants were analyzed by PCR. PCR results reveal six lines had VP2 gene in their genome. WT5 and WT39 lines were then cultivated to reach biomass enough for feeding chickens whose semm then were used as samples for ELISA tests. Initial results proved that WT5 line has had immune responses in the chickens fed the line.